Child fatality in families with prior CPS history: do those with and without intimate partner violence differ? - Jonson-Reid, Melissa (Journal of family violence, 2023)
Research indicates many children who experience maltreatment are also exposed to intimate partner violence (IPV). Some studies find that children with child protective services (CPS) history have higher risk of preventable child fatality (CF). It is not known if there are unique characteristics of families with combined CPS and IPV histories that could inform service plans to reduce risk of later CF. Information from documents published in the Innocents Lost Database was extracted and analyzed, and linked to county level census data. The sample includes CFs from 501 Florida families that occurred from 2008 to 2015. Families had a history of CPS contact, but cause of death varied. Bivariate (t-test, chi-square, correlation) and logistic regression analyses compared CF cases with and without IPV mentioned in the full sample (n = 501) and the reduced sample (n = 155 with in-depth documentation). Prevalence of IPV ranged from 34 to 46% (full and reduced sample respectively) with violent death more common for this group. CFs with noted IPV histories were more likely to involve school-aged children from larger families. Such cases were more likely to include primary caregivers with noted mental health and substance abuse concerns, and/or prior criminal justice system contact and secondary caregivers with criminal justice histories. IPV was common among preventable CFs with prior CPS histories. Caregivers in these families had substantial prior contact with both CPS and other adult service and criminal justice systems. Implications for risk screening and preventive services within adult-serving systems and schools are discussed.